Activatable Polymer Nanoenzymes for Photodynamic Immunometabolic Cancer Therapy. Issue 4 (11th December 2020) - Zeng, Ziling; Zhang, Chi; Li, Jingchao; Cui, Dong; Jiang, Yuyan; Pu, Kanyi
Abstract: Tumor immunometabolism contributes substantially to tumor proliferation and immune cell activity, and thus plays a crucial role in the efficacy of cancer immunotherapy. Modulation of immunometabolism to boost cancer immunotherapy is mostly based on small‐molecule inhibitors, which often encounter the issues of off‐target adverse effects, drug resistance, and unsustainable response. In contrast, enzymatic therapeutics can potentially bypass these limitations but has been less exploited. Herein, an organic polymer nanoenzyme (SPNK) with near‐infrared (NIR) photoactivatable immunotherapeutic effects is reported for photodynamic immunometabolic therapy. SPNK is composed of a semiconducting polymer core conjugated with kynureninase (KYNase) via PEGylated singlet oxygen ( 1 O2 ) cleavable linker. Upon NIR photoirradiation, SPNK generates 1 O2 not only to exert photodynamic effect to induce the immunogenic cell death of cancer, but also to unleash KYNase and trigger its activity to degrade the immunosuppressive kynurenine (Kyn). Such a combinational effect mediated by SPNK promotes the proliferation and infiltration of effector T cells, enhances systemic antitumor T cell immunity, and ultimately permits inhibition of both primary and distant tumors in living mice. Therefore, this study provides a promising photodynamic approach toward remotely controlled enzymatic immunomodulation for improved anticancer therapy. Abstract : An activatable organic nanoenzyme (SPNK) is developed for photodynamic immunometabolic cancer therapy. Near‐infrared photoirradiation of SPNK can not only induce immunogenic cell death by photodynamic therapy but also activate kynureninase to in situ degrade immunosuppressive kynurenine, leading to enhanced systemic antitumor immunity and inhibition of both primary and distant tumors.